LINC00536 knockdown inhibits breast cancer cells proliferation, invasion, and migration through regulation of the miR‐4282/centromere protein F axis - Mei‐Feng Zhou; Wei Wang; Lin Wang; Jin‐Dian Tan (Kaohsiung Journal of Medical Sciences, 2022)
Abstract Breast cancer (BC) poses a huge threat to women's health. Growing evidence has shown lncRNAs play critical roles in BC progression. However, the effect of LINC00536 in BC remains unknown. LINC00536, miR‐4282, and centromere protein F (CENPF) expressions in BC cells were determined using qPCR assay. Colony formation assay was employed to evaluate the cell proliferation of BC cells. Besides, cell migration and invasion were evaluated using the transwell assay. FISH assay was employed to analyze LINC00536 and miR‐4282 locations in BC cells. Additionally, dual luciferase reporter gene assay was performed to verify the binding relationships between LINC00536 and miR‐4282, miR‐4282 and CENPF. Here, our results displayed that LINC00536 and CENPF were overexpressed in BC cells, while miR‐4282 was downregulated. LINC00536 could negatively regulate miR‐4282 expression via directly binding to miR‐4282. LINC00536 silence suppressed the proliferation, migration, and invasion of BC cells, which was abolished by miR‐4282 inhibition. Additionally, miR‐4282 could negatively regulate CENPF expression via directly binding to CENPF. MiR‐4282 overexpression suppressed BC development, which was abolished by CENPF overexpression. Finally, we proved that LINC00536 silencing suppressed BC growth via regulating the miR‐4282/CENPF axis in vivo. Our research displayed that LINC00536 acted as an oncogene in BC. LINC00536‐enhanced BC cell proliferation, migration, and invasion. Moreover, LINC00536 functioned as a ceRNA to exert malignant characteristics in BC via the miR‐4282–CENPF axis. Collectively, our results demonstrated that the LINC00536–miR‐4282–CENPF axis was a critical player in BC development and was a promising target for BC therapy.